A Duoethnography on Disability and Allyship Within a Vision Science Doctoral Program: Perspectives on Inclusion, Diversity, Equity, and Accessibility - Natalina Martiniello; Walter Wittich (International Journal of Qualitative Methods, 2024)
People with visual impairments (those who are blind or who have low vision) continue to experience an unemployment rate of 70% or higher across all sectors but remain especially under-represented within higher education and the research ecosystem. Among the barriers emphasized by people with visual impairments are those related to accessibility and inclusion. It is within this socio-historical context that we began our interactions as a blind graduate student (Martiniello) and a sighted PhD. supervisor (Wittich) in the process of completing a doctoral program in vision science. Utilizing duoethnography as a methodological approach, we juxtapose two perspectives on a shared experience. Over a period of five years, we explored the ways in which our interactions as a trainee with lived experience and sighted ally have shaped our perspectives on disability inclusion in (and while doing) disability research and the role of allyship in the context of academia. We use examples from our lived experiences to illustrate the ways in which we negotiated the role of allyship throughout the research process, including the impact of accessibility and inclusion while completing a scoping review, semi-structured interviews and thematic content analysis. These collective experiences set the stage for new forms of advocacy and allyship to emerge. To the best of our knowledge, Dr Martiniello remains the first and only blind person to graduate in Canada with a PhD in Vision Science. Hopefully, she will not be the last.